Analisis Strategi Pemasaran Dalam Meningkatkan Penjualan Pada Toko Rafli Desa Tarailu Kabupaten Mamuju - Musyawarah, Irdha Yanti (Forecasting : Jurnal Ilmiah Ilmu Manajemen, 2023)
Rafli Store in Tarailu Village offers accessories products with various products, such as jewelry (earrings or studs, necklaces, bracelets, brooches), scarves, belts, suspenders, ties, scarves, gloves, handkerchiefs, bags, hats, glasses , belts, watches and pins, in addition to accessories, the Rafli Shop in Tarailu Village also offers game products for children aged three to six years such as picture puzzles, legos, rubik's cubes, dolls, stationery, musical instruments and many other types and kinds of children's games that consumers you can get it at the Rafli Shop in Tarailu Village in Mamuju Regency. The method used is a qualitative method by conducting direct interviews at the research site. There are several alternative data analyzes that can be used, namely: descriptive qualitative, descriptive comparative, qualitative or non-hypothetical. The strategic planning process consists of 1) data collection stage (evaluation of internal and external factors), analysis stage (SWOT Matrix, Internal External Matrix), and Internal and External Matrix. Based on the results of the research and discussion, several conclusions can be drawn as follows: 1) Rafli Shop in Tarailu Village, Mamuju Regency has the opportunity to increase turnover by maximizing sales, Rafli Shop in Tarailu Village, Mamuju Regency can work with distributor companies in adding game product variants children and other accessories, the Rafli Shop in Tarailu Village, Mamuju Regency, is expected to improve services by providing a guarantee of returning goods if there is product damage which is the source of the shop's fault. 2) The Rafli Shop in Tarailu Village, Mamuju Regency, still has a threat in increasing sales of children's game products and accessories, because there is no guarantee that there will be no competitors selling the same product in the future. a few where there are only two people in providing sales services to consumers, while the obstacles that are still experienced by the Rafli Shop in Tarailu Village, Mamuju Regency are delays in the distribution of partners in fulfilling goods whose stock has been sold out at the Rafli Shop in Tarailu Village, Mamuju Regency. Keywords: marketing strategy, and increasing sales